Mediating sustainability in the consumer society - Stuedahl, Dagny; Nielsen, Liv Merete; Berg, Lisbeth Løvbak; Skjerven, Astrid, 1953- (Routledge, 2024)
"This book sheds light on the role and impact of sustainability mediation, an effective tool for political authorities and business enterprises to persuade consumers of the integrity of their actions, products, and services. In this era of ecological and societal crises fuelled by increasing consumption, sustainability has become a key buzzword and target to attain. Governments around the world argue that they will meet their sustainability goals through environmental actions, by enabling consumers to make better choices and expecting brands to respond accordingly. At the same time, consumers are overwhelmed by the messaging conveyed in sustainability marketing campaigns, often featuring misleading greenwashing, with political authorities, organisations, and business enterprises all having conflicting interests. In this complex scenario, mediation has become a crucial issue. This book offers a critical and multidisciplinary view of sustainability mediation from experts in the fields of philosophy, consumption research, media studies, fashion, design, and citizenship, offering a unique, holistic view. Each chapter highlights different and problematic aspects of the cultural narratives being communicated, for example the necessity of growth and the notion of a green economy. They present current theories, methods, indicators, and strategies used to assess and measure the relation between mediation, behaviour, and sustainable development. The book is of interest to scholars, researchers, and postgraduate students in all subject fields concerned with sustainability, including design, visual communication, fashion, consumption, media and journalism, and sustainable development"-- Provided by publisher.
Keywords: Sustainable development.; Environmentalism in mass media.; Consumer behavior -- Environmental aspects.; Consumption (Economics) -- Environmental aspects.; elektronické knihy; electronic books